2018
DOI: 10.1051/matecconf/201815005070
|View full text |Cite
|
Sign up to set email alerts
|

Can Retail Selling Prices of Petrol and Diesel Trigger Inflation in Malaysia?

Abstract: Previously, many studies explored the effects of oil price on inflation by using the price of crude oil as the proxy of oil price. The novelty of this current study is that it used several types of fuel prices including RON95, RON97 and Diesel. This study employed the ARDL approach and analysed the monthly data from 2010 to 2015 in Malaysia. The result shows that there are significant effects of the price of RON95, RON97 and diesel on inflation in the long run in Malaysia. However, in the short run, the price … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Using linear ARDL model, the study found that the impact of oil price changes on inflation expectations is more intense when oil prices are above a threshold of 67 USD per barrel. Shaari et al (2018) investigated the effects of retail selling prices of petrol and diesel on inflation in Malaysia using monthly data from 2010 to 2015. The ARDL result shows that there are significant effects of retail selling prices of petrol and diesel on inflation in the long run.…”
Section: Empirical Review On Oil Price and Consumer Pricesmentioning
confidence: 99%
“…Using linear ARDL model, the study found that the impact of oil price changes on inflation expectations is more intense when oil prices are above a threshold of 67 USD per barrel. Shaari et al (2018) investigated the effects of retail selling prices of petrol and diesel on inflation in Malaysia using monthly data from 2010 to 2015. The ARDL result shows that there are significant effects of retail selling prices of petrol and diesel on inflation in the long run.…”
Section: Empirical Review On Oil Price and Consumer Pricesmentioning
confidence: 99%